Laser–tissue interaction simulation considering skin-specific data to predict photothermal damage lesions during laser irradiation. Issue 3 (13th April 2023) - Kim, Hyo-Jin; Um, Seung-Hoon; Kang, Yong Guk; Shin, Minwoo; Jeon, Hojeong; Kim, Beop-Min; Lee, Deukhee; Yoon, Kyungho
Abstract: This study aimed to develop a simulation model that accounts for skin-specific properties in order to predict photothermal damage during skin laser treatment. To construct a computational model, surface geometry information was obtained from an optical coherence tomography image, and the absorption coefficient of the skin was determined through spectrophotometry. The distribution of the internal light dose inside the skin medium was calculated using the light propagation model based on the Monte Carlo method. The photothermal response due to the absorption of laser light was modeled by a finite difference time domain model to solve the bio-heat transfer equation. The predicted depth and area of the damaged lesions from the simulation model were compared to those measured in ex vivo porcine skin. The present simulation model gave acceptable predictions with differences of approximately ∼10% in both depth and area. Graphical Abstract: